2015
DOI: 10.1177/230949901502300228
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Open Transthoracic Approach for Resection of a Calcified Herniated Thoracic Disc and Repair of the Dural Surface with Fibrin Glue: A Case Report

Abstract: This study reports a case of severe anterior compression of the spinal cord by a calcified herniated thoracic disc at the T9/10 level in a 46-yearold woman. She underwent resection of the calcified herniated thoracic disc and the integrated dura, using a microscopically assisted mini-open transthoracic approach. The remaining dura mater was shaped and repaired by alternate overlapping without suture. The dural surface was reinforced with a combination of fibrin glue and a polyglycolic acid sheet. This novel pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Recently, they reported that it was safe and effective for gradual spinal cord decompression through migration of floated plaques after anterior decompression via a posterolateral approach for OPLL in the thoracic spine [ 16 ]. Besides, they reported in another study [ 17 ] a case of severe anterior compression of the spinal cord by a calcified herniated thoracic disc at the T9/10 level in a 46-year-old woman. They performed resection of the calcified herniated thoracic disc and the integrated dura, using a microscopically assisted mini-open transthoracic approach in which the rib bone was partially drilled to widen the operative field, which was a successful attempt.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, they reported that it was safe and effective for gradual spinal cord decompression through migration of floated plaques after anterior decompression via a posterolateral approach for OPLL in the thoracic spine [ 16 ]. Besides, they reported in another study [ 17 ] a case of severe anterior compression of the spinal cord by a calcified herniated thoracic disc at the T9/10 level in a 46-year-old woman. They performed resection of the calcified herniated thoracic disc and the integrated dura, using a microscopically assisted mini-open transthoracic approach in which the rib bone was partially drilled to widen the operative field, which was a successful attempt.…”
Section: Discussionmentioning
confidence: 99%